HARMONIZATION OF FAMILY INFLUENCED THE DEVELOPMENT OF THE SOUL AND PSYCHE OF THE CHILD IN ISLAM - Hamka, Husain (Journal of Humanity, 2013)
This research from the outline of the problem how can Islamic view on the influence on the development of harmonious family life and children, as well as mental factors are affecting the family in order to harmonize the soul and mental coaching children. This research includes research library (Library research) with the data collection method that uses some of the literature. Data analysis using the method of inductive, deductive engineering and comparative. The results showed Islam looked at that childs soul and mental Coaching is done first in family environment as founders. To develop the spiritual aspects of the child properly, then the family must be created in harmony with the way each family member can perform the function and role Factors that can affect the creation of a harmonious family life and in coaching mentally children are internal factors are factors that are sourced from within the family environment, and external factors such as family environment, namely the public influence of the development of science and technology,